2014
DOI: 10.1093/femsec/fiu002
|View full text |Cite
|
Sign up to set email alerts
|

Altered gut microbial energy and metabolism in children with non-alcoholic fatty liver disease

Abstract: Obesity is becoming the new pediatric epidemic. Non-alcoholic fatty liver disease (NAFLD) is frequently associated with obesity, and has become the most common cause of pediatric liver disease. The gut microbiome is the major metabolic organ and determines how calories are processed, serving as a caloric gate, and contributing towards the pathogenesis of NAFLD. The goal of this study is to examine gut microbial profiles in children with NAFLD using phylogenetic, metabolomic, metagenomic, and proteomic approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
217
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(237 citation statements)
references
References 52 publications
13
217
2
5
Order By: Relevance
“…This is a clear indication that the microbiome of ob/ob mice produces a similar amount of alcohol as the microbiome of lean animals. This observation contrasts with the report that the stools of patients with NAFLD exhibit higher levels of alcohol than that of the healthy subjects 4. In fact, two groups reported that the faecal microbiota in NAFLD has higher representations in alcohol producing microbes 4 5.…”
contrasting
confidence: 74%
See 1 more Smart Citation
“…This is a clear indication that the microbiome of ob/ob mice produces a similar amount of alcohol as the microbiome of lean animals. This observation contrasts with the report that the stools of patients with NAFLD exhibit higher levels of alcohol than that of the healthy subjects 4. In fact, two groups reported that the faecal microbiota in NAFLD has higher representations in alcohol producing microbes 4 5.…”
contrasting
confidence: 74%
“…2), including the group led by Bergheim, who first reported elevated serum alcohol in NAFLD 3. Previous studies indicated that the elevated alcohol level in NAFLD is associated with increased representation of alcohol producing bacteria in the gut microbiome 4 5. However, a recent report by Bergheim and her colleagues suggested a very different mechanism for the alcohol spike in NAFLD 6.…”
mentioning
confidence: 99%
“…It therefore appears that levels and subtypes of SCFAs correlate with the severity of fatty liver disease. However, another study reported that some SCFAs, especially formate, acetate and valerate, were less abundant in faecal samples from children with NAFLD 109. These apparent differences might be due to differences in patient age, but could also be related to differences in diet, environmental factors and technical issues.…”
Section: Microbiota-derived Metabolites In Nafldmentioning
confidence: 98%
“…In one survey, obese children with NAFLD had a greater abundance of Gammaproteobacteria and Prevotella in the stool microbiome and significantly higher levels of ethanol in the stool metabolome compared to lean healthy children [23] . In another survey, the phylum Proteobacteria , and in particular, the taxa Enterobacteriaceae and Escherichia were increased in abundance in the gut microbiota of children with NASH compared to obese individuals, while obese and NASH children showed greater abundance of Bacteroidetes , predominantly Prevotella , compared to lean children [24] .…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%